Culture Codes and Their Representation in Stable Word Complexes (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyzes stable word complexes as language symbols that verbalize the system of language codes.
Keywords: culture codes; the system of language codes; stable word complexes